Inhibitive effect of Cocon nucifera L. (coconut pulp) extract on mild steel acid corrosion - Sobri, Shafreeza; Rahim, Norin Hafizah (2015)
Corrosion control method, especially the use of inhibitors has gained monumental importance nowadays. The demand for green inhibitor to replace toxic one has increased tremendously. The use of local wastes which are organic in nature for the production of green corrosion inhibitor is no doubt the trend of the day. To arrive at an inexpensive non-toxic, eco-friendly inhibitor formulation, the present study on the use of Coconut pulp waste extract of Cocon Nucifera L. has been carried out by the weight loss method. The aim of this project is to study the inhibitive effect in terms of time and concentration of the Coconut pulp waste extract on the acid corrosion of mild steel in 1.0 M HCL solution. The results of study showed that as the concentration of the inhibitor increases, the rate of corrosion decreases. It also showed that as the concentration of the inhibitor increases, the inhibitor efficiency also increases up to an optimum of approximately 95 %. Examination on the extract by Fourier transform infrared (FTIR) spectroscopy and Scanning electron microscopy (SEM) studies confirm that deposition of coconut pulp extract on the metal surface. The result from this study revealed that the extract of coconut pulp waste proved to be highly economical, eco-friendly and non-toxic corrosion inhibitor.